KenyaEclipse learning to program in eclipse. - Chatley, Robert (Software engineering notes.)
A fundamental part of a Computer Science degree is learning to program. Rather than starting students on a full commercial language, we favour using a dedicated "teaching language" to introduce programming concepts.At the same time, we want to introduce students to popular tools that assist in the software development process. However, up until now our teaching language, Kenya, has not been supported by professional IDEs. Therefore, we have been unable to progress smoothly from first principles to the state of the art within one environment.We present work that integrates the Kenya language into the Eclipse environment. Students can now become familiar with the major features of a professional IDE while learning to program, and experience a smooth transition to commercial languages within the same environment.One of the hardest things to teach students is good programming style. Compilers reveal syntactic and type errors, but do not analyse style. We have harnessed as-you-type code checking, as seen in Eclipse's Java development tools, to provide advice on program style as well as correctness.